Diagnóstico de sostenibilidad ambiental para la comunidad pesquera del municipio de Tubará - Atlántico, Colombia. (2019)
Although fishing is a livelihood for many people in different areas of the country, there has been a lack of awareness of the current situations of artisanal fishermen, which has had an impact on fisheries management policies and programmes do not conform to the real conditions of these communities. Different factors such as resource exploitation, poor fishing practices, environmental impacts, poverty rates, lack of education and development opportunities have negatively influenced their activity is threatened and far from being called sustainable fishing. In this sense, the research was based on the development of a sustainability diagnosis for the fishing community of the municipality of Tubará, through the elaboration of a materiality matrix to give birth to the adaptation of a methodology used for the reporting of the environmental sustainability at the business level called the GRI G4 methodology, which applies the identification of the most relevant aspects for the fishing community and defined stakeholders. As a result of the research, it was obtained that the material aspects for the fishing community and territorial authorities are: the importance of fishing problems, safety in fisheries, education, basic services, accompaniment of entities to fishing communities and the economy. These material aspects reflected the current social, economic and environmental conditions of the community, therefore it can be said that the adaptation of this methodology can be implemented in communities.